Changes in Rats’ Liver Structure Induced by Zinc Oxide Nanoparticles and the Possible Protective Role of Vitamin E - Abdelmonem A. Hegazy; Marwa M. Ahmed; Mohammed A. Shehata; Marwa M. Abdelfattah (International Journal of Human Anatomy, 2018)
Background: Oral ingestion of zinc oxide nanoparticles (ZnONPs) may lead to serious liver injury. Vitamin E (VE) is an important antioxidant factor that can reduce such damage. Aim: This study aimed to evaluate the possible changes that could take place in the liver of adult male albino rats after oral ingestion of ZnONPs and elucidate the potential protective role of VE against such damage. Material and Methods: Forty eight male albino rats were divided into four groups of 12 animals each. Group (1) served as control group and received normal saline. Group (2) “VE-treated” received 100 mg/kg/day of VE dissolved in normal saline by oral gavage for 21 days. Group (3) “ZnONPs-treated” received a daily dose of ZnONPs dispersed in the fresh sterilized physiological saline solution 1mg/kg for 5 constitutive days. Group (4) “concomitant ZnONPs and VE-treated” was pretreated with VE 100 mg/kg/day for 14 days followed by the same dose of ZnONPs as in group (3) for 5 days. The extent of hepatic damage was evaluated by histological and immunohistochemical examination of liver samples and serological analysis of liver enzymes. Results: Body weights and liver weights showed very highly significant decrease (P <0.001) in the ZnONPs-treated group. The histological results in ZnONPs-treated group revealed congested dilated central veins and blood sinusoids, loss of normal arrangement of hepatocytes and most of hepatocytes showed marked vacuolated cytoplasm with darkly stained nuclei. Portal area affection was in the form of congested dilated portal veins with bile duct hyperplasia and cellular infiltration. There was an increase in the mount of blue stained collagen fibers around central veins together with strong positive reaction for Caspase 3 in ZnONPs-treated group. Similarly biochemical analysis indicated that the levels of serum aminotransferase (AST &ALT) significantly increased in ZnONPs-treated group when compared with other groups. Rats pretreated with VE showed improvement of the histological findings and biochemical parameters. Conclusion: Ingestion of ZnONPs could be associated with serious liver affection and pretreatment with VE is suggested to induce some improvement of such deleterious changes.
Keywords: Rat liver